Doppler Evaluation of Uterine Arteries in Different Phases of Menstrual Cycle in Young Adult Females with Regular Cycles - Ayesha Mubashra, Zeeshan Haider, Hamnah Fatima, Saad Qayyum, Mehreen Fatima, Syed Muhammad Yousaf Farooq, Hafiz Ahmad Din, Kulsoom Zamani, Muhammad Uzair, Rida Javed, Samia Shahid, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The menstrual cycle is nature's cyclical method of getting ready for pregnancy. The uterine lining grows each month in preparation for implantation by a fertilized ovum. Cyclic endometrium may be non-invasively assessed with Doppler sonography and leads to alterations in local vascular patterns. The pulsatility index (PI), which measures the uterine artery (UtA) impedance, displays a predictable pattern during the typical menstrual cycle. Aim: To evaluate the flow of blood through the uterine arteries in young adult women with regular cycles during various menstrual cycle stages. Place of study and duration of study: Department of Radiology, University Ultrasonography Clinic in Green Town, Lahore. Between January 2022 and October 2022. Methodology: A comparative study was carried out at the University Ultrasonography Clinic in Green Town, Lahore, Pakistan. In this study, 180 patients between the ages of 16 and 35 were enrolled using a convenient sampling technique.All the married, and unmarried ages between 13- and 40 years old having regular periods once a month were involved in this study. Results: 180 patients in all were involved in this study comprising 60 females of each phase of the menstrual phase, 23 patients age were 25 age, 19 patients were 23 age, 20 patients were 18 age, 15 patients were 22, and 9 patients were the age of 29,30,31 years. RI of the right ovary was 0.5938 ± 0.8, the mean RI of the left ovary was 6.5083 ± 0.92357 forthe 10-20 days phase cycle, RI of the right ovary was 0.5937 ± .05266, the mean RI of the left ovary was 10.6967 ± 1.13466 of 11-20 days phase cycle, RI of right ovary was 0.5925 ± .05423, mean RI of left ovary was 6.7083±1.10258 of 21-30 days phase cycle.The uterine artery's resistivity index is compared in three menstrual cycle phases which are days 1 to 10, 11 to 20, and 21 to 30. No statistical difference was found in the right three means of the uterine artery's resistivity index as P-value=0.989 > ∞=0.05. The averages of the Resistivity index of the uterine artery(left)in the three phases of the menstrual cycle are proved to be equal as we failed to find statistically significant differences where P-value=0.975 > ∞=0.050. Conclusion: In this study, we have concluded that endometrial thickness and uterine artery resistivity index, determined ultrasonographically depend upon the phase of the menstrual cycle. The endometrialthickness progressively increases throughout the menstrual phase with no change in the resistive index of both uterine arteries. Keywords: Doppler ultrasound, uterine arteries, resistive index, pulsative index, endometrium stripe thickness.